Electrophysical properties of heterostructures CuS/ZnS and PCTFE–CuS/ZnS system - S. L. Prokopenko; G. M. Gunja; S. N. Makhno; P. P. Gorbyk (Хімія, фізика та технологія поверхні)
In order to synthesize the polymer composite system of the PCTFE–CuS/ZnS, the nanodispersed ZnS was synthesized by hydrothermal method afterwards heterostructures of CuS/ZnS were obtained using ion-substitution mechanism. The concentration dependence of the real and the imaginary components of the complex dielectric permeability and electrical conductivity of synthesized samples were investigated. Obtained composites have high values of the dielectric permeability at high frequencies and conductivity at low frequencies. At 50 % (molar) substitution of Zn ions by Cu the percolation threshold was determined at the volumetric content of CuS about 0.06.